Peran Guru PJOK dalam Mengimplementasikan Profil Lulusan Dimensi Kolaborasi - Tanto Setyawan; Iis Marwan; Juhrodin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to describe the strategies used by Physical Education (PJOK) teachers in implementing the collaboration dimension of the Graduate Profile, the forms of facilitation and intervention provided during the learning process, as well as the challenges encountered and the solutions applied in elementary schools across Suakamanah Village, Cigalontang District, Tasikmalaya Regency. This research employed a qualitative approach with a phenomenological method to explore in depth the real experiences of three PJOK teachers as respondents. Data were collected through in-depth interviews, classroom observations, and documentation of instructional materials, and were analyzed using data reduction, data display, and conclusion-drawing techniques. The results indicate that teachers designed collaborative learning through the development of lesson plans that explicitly incorporate indicators of teamwork, the use of Cooperative Learning, Problem-Based Learning, and Project-Based Learning models, the formation of heterogeneous groups, and the modification of games to accommodate limited facilities and space. During implementation, teachers facilitated communication and group interaction, assigned clear roles, and provided interventions for passive or dominant students as well as groups experiencing conflict. The main challenges faced included limited equipment and space, diverse student characteristics, restricted instructional time, and administrative demands; however, teachers were able to address these obstacles through creativity, personal approaches, and effective time management. This study concludes that PJOK learning plays a strategic role in developing students’ collaboration dimension and can be implemented effectively despite various contextual limitations. Keywords : Teacher Roles; Graduate Profile; Collaboration Dimension.